SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166305-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Decision-Making in Reservoir Managment Using Reduced-Order Models

Abstract: Reduced-order models (ROM) are considered powerful techniques to address computational challenges associated with reser-voir management decision-making. In this sense, they represent perfect alternatives that trade off accuracy for speed in a controllable manner. In this paper, we describe a model-order reduction technique that entails the use of proper orthogonal decomposition (POD), truncated balanced realization (TBR) and discrete empirical interpolation (DEIM) to accurately re-produce the full-order model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In work carried out by Cardoso and Durlofsky [150], a POD in combination with TPWL could increase the speedup for the same reservoir discussed earlier from a factor of 10 to 450. Additionally, the application of DEIM and POD is applied in some studies to create proxies for reservoir simulation [156,157], fluid flow in porous media [158,159], and water flooding optimization [160].…”
Section: Reduced-order Models (Rom)mentioning
confidence: 99%
See 1 more Smart Citation
“…In work carried out by Cardoso and Durlofsky [150], a POD in combination with TPWL could increase the speedup for the same reservoir discussed earlier from a factor of 10 to 450. Additionally, the application of DEIM and POD is applied in some studies to create proxies for reservoir simulation [156,157], fluid flow in porous media [158,159], and water flooding optimization [160].…”
Section: Reduced-order Models (Rom)mentioning
confidence: 99%
“…Other methods to treat the non-linearity can be pointed out, such as Gauss-Newton with approximated tensors [161], truncated balanced realization [160], localized discrete empirical interpolation method [162], trajectory piecewise quadratic [163], and sparse proper orthogonal decomposition-Galerkin [164]. A comprehensive study of these methods in reservoir modeling can be found in work carried out by Suwartadi [165] and He [166].…”
Section: Reduced-order Models (Rom)mentioning
confidence: 99%
“…ROMs are physics-based models derived from distributed features along model and its basic concepts (Udy et al 2017). It transforms FOM to a lower dimensions space in order to reduce the number of variables that must be calculated and as a result computing time will be lower (Alghareeb and Williams 2013). Thus, there are two objectives in constructing a ROM; providing a high-precision description of system dynamics at a much lower computational cost than the original numerical model and providing a tool that can easily interpret the system dynamics with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of subsurface flow problems, Chaturantabut and Sorensen (2011) applied DEIM for model reduction of viscous fingering problems of an incompressible fluid through a two-dimensional homogeneous porous medium. Alghareeb and Williams (2013) combined DEIM with POD procedures, and the resultant reduced model was applied in waterflood optimization problem. Recently, Ghasemi (2015) applied POD with DEIM to an optimal control problem governed by two-phase flow in a porous media.…”
Section: Introductionmentioning
confidence: 99%